Needs analysis study: Integrating nationalism into Pancasila education - Fitriyah, Arikah Nur; Sukriono, Didik; Mardhatillah, Mardhatillah (Univeritas Papua, 2025)
This study aims to analyze elementary school students' attitudes toward nationalism, both in terms of understanding and implementation. This is a mixed-method study combining quantitative and qualitative data. The participants consisted of 54 fifth-grade students at SDN Kauman 1 in Malang City, selected using purposive sampling. The methods used to collect data included interviews, observations, and questionnaires. Students' understanding of nationalistic attitudes was found to be quite good; however, the implementation of these attitudes was still lacking. Students' understanding of nationalistic attitudes was assessed through a questionnaire consisting of 7 indicators with 15 statements, with 5 indicators receiving “strongly agree” responses from over 50% of participants. Furthermore, the implementation of nationalistic attitudes was obtained from observations during the learning process of the Pancasila education subject and interviews to reinforce the information found by the researcher during the observation. Further research can use the results of this study to develop learning media that are appropriate to the needs and actual conditions in the field, utilizing the results of the needs analysis conducted in this study.